2018
DOI: 10.1016/j.drugalcdep.2017.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Male-female differences in the onset of heavy drinking episode soon after first full drink in contemporary United States: From early adolescence to young adulthood

Abstract: Based on recent survey data from the US, this study's survival analyses support early adolescent female excess in the onset of HDE. When drinking starts at or after age 15 years, a male excess becomes apparent within two years since first full drink. Future studies may probe any sex-specific mechanisms toward the rapid onset of HDE at different age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…For example, MTF data indicate that in recent years, older adolescent boys were likelier to engage in drinking, binge drinking, and high‐intensity drinking than girls (Patrick and Terry‐McElrath, ; Patrick et al., ; Schulenberg et al., ). However, since approximately 2002, younger adolescent girls report higher levels of drinking incidence (e.g., taking the first full drink) than boys; specifically, 2 studies found that the rate of newly incident drinking among female adolescents exceeded that among male adolescents by 2% (Cheng and Anthony, , ; Seedall and Anthony, ).…”
Section: Adolescencementioning
confidence: 99%
“…For example, MTF data indicate that in recent years, older adolescent boys were likelier to engage in drinking, binge drinking, and high‐intensity drinking than girls (Patrick and Terry‐McElrath, ; Patrick et al., ; Schulenberg et al., ). However, since approximately 2002, younger adolescent girls report higher levels of drinking incidence (e.g., taking the first full drink) than boys; specifically, 2 studies found that the rate of newly incident drinking among female adolescents exceeded that among male adolescents by 2% (Cheng and Anthony, , ; Seedall and Anthony, ).…”
Section: Adolescencementioning
confidence: 99%
“…6 Although more boys (19%) than girls (13%) start drinking before age 14, girls who begin drinking in early adolescence have a shorter time period between first drink and first episode of binge drinking. 6 , 18 In contrast, when drinking starts at age 15 or later, males progress more quickly to binge drinking.…”
Section: Adolescentsmentioning
confidence: 99%
“…Additionally, the national trends in Norway show that more boys than girls have started drinking in 8 th grade, while girls exceed boys in alcohol drinking in 9 th (Bakken, 2018). One explanation for why girls drink more than boys once they have onset drinking could be the reduced stigma against female drinking (Cheng & Anthony, 2018). Another explanation might be linked to the early sexual maturation among girls (Bratberg et al, 2005) that again could lead to an easier access to alcohol through older friends or romantic partners.…”
Section: Gender Differences In Alcohol Consumption and The Tpb Relatimentioning
confidence: 99%